Association of the android to gynoid fat ratio with nonalcoholic fatty liver disease: a cross-sectional study - Yang, Ling; Huang, Hangkai; Liu, Zhening; Ruan, Jiaqi; Xu, Chengfu (Frontiers in Nutrition, 2023)
Background Nonalcoholic fatty liver disease (NAFLD) is becoming a severe global public health problem, and can developed into fibrotic nonalcoholic steatohepatitis (NASH), but its risk factors have not been fully identified. The objective of this study was to investigate the association between the android-to-gynoid fat ratio (A/G ratio) and the prevalence of NAFLD. Methods This cross-sectional study is based on the 2003–2006 and 2011–2018 cycles of the National Health and Nutrition Examination Survey and included 10,989 participants. Participants aged 20 and older without viral hepatitis or significant alcohol consumption were included. Dual-energy X-ray absorptiometry was used to assess body composition. NAFLD was diagnosed using the United States fatty liver index (US FLI). Multivariable logistic regression models were used to evaluate the association between the A/G ratio and NAFLD. Results The prevalence of NAFLD was 32.15% among the study population. Android percent fat and the A/G ratio were significantly higher in patients with NAFLD than in those without NAFLD [41.68% (0.25) vs. 32.80% (0.27), p < 0.001; 1.14 ± 0.01 vs. 0.94 ± 0.00, p < 0.001, respectively]. Logistic regression analysis showed that android percent fat was positively correlated to NAFLD (OR: 1.15, 95% CI: 1.11–1.18), while gynoid percent fat was negatively correlated to NAFLD (OR: 0.92, 95% CI: 0.90–0.94), and the A/G ratio was significantly associated with the prevalence of NAFLD (OR: 1.59, 95% CI: 1.38–1.82) and fibrotic NASH (OR: 2.01, 95% CI: 1.71–2.38). We also found that females had a notably diminished A/G ratio compared with males (0.91 vs. 1.12, p < 0.001). In addition, the female population proportion was negatively correlated with the A/G ratio, which may partly explain the lower prevalence of NAFLD in females. What is more, the OR value of the A/G ratio in the female subgroup was much higher than that in the male subgroup in all adjusted models. Conclusion A/G ratio is significantly associated with NAFLD and fibrotic NASH. Women have a lower A/G ratio than men, which may explain the sex difference in NAFLD prevalence. Furthermore, with a higher A/G ratio, the association between females and NAFLD are greatly elevated.